Mechanisms of Salt Tolerance and Molecular Breeding of Salt-Tolerant Ornamental Plants - Guo, Jianrong; Shan, Changdan; Zhang, Yifan; Wang, Xinlei; Tian, Huaying; Han, Guoliang; Zhang, Yi; Wang, Baoshan (Frontiers in Plant Science, 2022)
As the area of salinized soils increases, and freshwater becomes more scarcer worldwide, an urgent measure for agricultural production is to use salinized land and conserve freshwater resources. Ornamental flowering plants, such as carnations, roses, chrysanthemums, and gerberas, are found around the world and have high economic, ornamental, ecological, and edible value. It is therefore prudent to improve the salt tolerance of these important horticultural crops. Here, we summarize the salt-adaptive mechanisms, genes, and molecular breeding of ornamental flowering crops. We also review the genome editing technologies that provide us with the means to obtain novel varieties with high salinity tolerance and improved utility value, and discuss future directions of research into ornamental plants like salt exclusion mechanism. We considered that the salt exclusion mechanism in ornamental flowering plants, the acquisition of flowers with high quality and novel color under salinity condition through gene editing techniques should be focused on for the future research.